2017
DOI: 10.1515/cerce-2017-0032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deficit Irrigation on Raised Bed Wheat Cultivation

Abstract: ABSTRACT.The experiment was conducted during Rabi season of 2015-2016 and 2016-2017 at the Regional Agricultural Research station, BARI, Ishurdi, Pabna, Bangladesh, to determine the water requirements of wheat on raised bed and the effect of different deficit irrigation on yield, water use efficiency and applied water productivity under raised bed wheat. This study consisted of following irrigation treatments: T 1 = Irrigations up to 100% field capacity (FC) at crown root initiation (CRI), botting and grain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…For example, Eissa and Roshdy selected maize to show the best rate of nitrogen quantity by using two various deficit irrigation; however, they did not select more than one to show the similarities and differences between them relative to nitrogen and/or other parameters by choosing many deficit irrigation levels [13]. Similarly, Zaman et al used one crop (bed wheat) to show the effect of four deficit irrigation levels on the properties of the plant, such as height, grain yield, and spike per meter square, which means they did not mention to other crops relative to their properties when using different stages of irrigation water [19].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Eissa and Roshdy selected maize to show the best rate of nitrogen quantity by using two various deficit irrigation; however, they did not select more than one to show the similarities and differences between them relative to nitrogen and/or other parameters by choosing many deficit irrigation levels [13]. Similarly, Zaman et al used one crop (bed wheat) to show the effect of four deficit irrigation levels on the properties of the plant, such as height, grain yield, and spike per meter square, which means they did not mention to other crops relative to their properties when using different stages of irrigation water [19].…”
Section: Resultsmentioning
confidence: 99%
“…Paucity irrigation has been applied in many crops to save water and to achieve water use efficiency in crops such as Phillyrea angustifolia [7], Beta vulgaris L. var. cicla [8], sugar beet [9], maize [10][11][12][13][14], corn [15], wheat [16][17][18][19], potato [20][21][22], onion [23], cucumber [24], olive trees [25], almond [26], plum fruit [27], tomato [28], and other species.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Islam (2016) also reported that the yield of lentil was higher by 23% in ST and 18% in BP compared with CT for lentil. Besides, Zaman et al (2017) reported that at raised bed wheat cultivation increasing 15.66% grain yield than CT. Saeed (2013) also reported that, yield of wheat with happy seeder were 18% and 15% higher than minimum and conventional tillage respectively.…”
Section: Weather and Climate Of Growing Sessionmentioning
confidence: 98%